Caring for children born with cleft lip and palate within the Nigerian health care system - A T Adeyemi; B O Akintububo (Wolters Kluwer Medknow Publications, 2016)
Background: Children affected with cleft lip and/or palate often present with difficulties in feeding, hearing, speech, and dental occlusion. Caring for these children starts at birth and aims at providing holistic treatment so that they can live a normal life. Shortcomings of cleft care services in Nigeria have been reported previously and include lack of comprehensive care, shortage of personnel and equipment as well as difficulty in accessing services. Accessing governmental funding may impact greatly on the quality of services being provided and may solve many problems associated with cleft care. One way of accessing governmental funding in Nigeria is through health parastatals and agencies which have resources to fund health care and may possibly fund cleft care if they are well informed. The aim of this study is to discuss the possible ways that cleft care may be integrated into the Nigerian health care system to allow for governmental funding. Materials and Methods: This study employed a narrative literature review method, using key search terms to collect useful information in Nigeria about cleft care, health care system, and funding. Salient points concerning the organization of the Nigerian health care system and the place of cleft care were identified; these have been summarized and reported. Results: The Nigerian health care system operates at three levels: Tertiary, secondary, and primary. Cleft care services are available at the tertiary and secondary levels only, and rarely at the primary level, where majority of affected children are recruited for surgical repair. The Nigerian government does not fund cleft care services; funding is mainly from donor agencies or borne on an "out-of-pocket basis." Conclusion: This study has reported useful information on how cleft care can be integrated into the current health care system in Nigeria that may serve as a useful guide when planning health policies.